T and B lymphocytes in patients with chronic active hepatitis (CAH). - Colombo, M (1977)
Absolute numbers of T and B lymphocytes as well as active E rosette-forming cells were measured in twenty-seven patients with chronic active hepatitis (CAH), and in thirty control patients. In patients with CAH without cirrhosis, active E rosette-forming cells (a subpopulation of T lymphocytes considered to be actively involved in cell-mediated immune reactions) as well as lymphocytes with surface markers for IgA, IgM and IgG were increased. In patients with CAH and cirrhosis, total T lymphocytes were decreased. These results emphasize the significance of lymphocytes in CAH, and suggest the importance of monitoring T- and B-cell populations in patients with this disease.